2015
DOI: 10.1002/2015ja021310
|View full text |Cite
|
Sign up to set email alerts
|

Response of the topside and bottomside ionosphere at low and middle latitudes to the October 2003 superstorms

Abstract: Ionospheric observations from the ground‐based GPS receiver network, CHAMP and GRACE satellites and ionosondes were used to examine topside and bottomside ionospheric variations at low and middle latitudes over the Pacific and American sectors during the October 2003 superstorms. The latitudinal variation and the storm time response of the ground‐based GPS total electron content (TEC) were generally consistent with those of the CHAMP and GRACE up‐looking TEC. The TECs at heights below the satellite altitudes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
72
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 34 publications
2
72
0
Order By: Relevance
“…Previous studies have demonstrated both the positive correlation between TEC and foF2 at high and middle latitudes during many storm events and no evident correlation between TEC and foF2 at low and middle latitudes during some storms (Maruyama et al, 2004;Liu et al, 2012). Recent studies (Astafyeva et al, 2015;Lei et al, 2015;Liu et al 2015) demonstrate that the topside and bottomside ionosphere can react with opposite sign to a geomagnetic storm, which complicates the understanding of how these parts can finally contribute to the storm-time TEC variation. Several important issues regarding the relationship between foF2 and TEC disturbances are still unresolved: (1) what is the global relationship between foF2 and TEC response to geomagnetic storms, and (2) how does this relationship vary with time, storm phase, longitude and latitude?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated both the positive correlation between TEC and foF2 at high and middle latitudes during many storm events and no evident correlation between TEC and foF2 at low and middle latitudes during some storms (Maruyama et al, 2004;Liu et al, 2012). Recent studies (Astafyeva et al, 2015;Lei et al, 2015;Liu et al 2015) demonstrate that the topside and bottomside ionosphere can react with opposite sign to a geomagnetic storm, which complicates the understanding of how these parts can finally contribute to the storm-time TEC variation. Several important issues regarding the relationship between foF2 and TEC disturbances are still unresolved: (1) what is the global relationship between foF2 and TEC response to geomagnetic storms, and (2) how does this relationship vary with time, storm phase, longitude and latitude?…”
Section: Introductionmentioning
confidence: 99%
“…This effect is even more pronounced during nighttime at the solar activity minimum, where the plasmaspheric contribution to TEC can exceed the ionospheric one (Lunt et al, 1999a, b;Cherniak et al, 2012;Klimenko et al, 2015c). In fact, the TEC variability depends on the lower and topside ionosphere as well as the plasmasphere (Balan et al, 2002;Gulyaeva and Gallagher, 2007;Yizengaw et al, 2008;Cherniak et al, 2012;Lee et al, 2013;Zakharenkova et al, 2013;Klimenko et al, 2015b, c;Lei et al, 2015). Previous studies have demonstrated both the positive correlation between TEC and foF2 at high and middle latitudes during many storm events and no evident correlation between TEC and foF2 at low and middle latitudes during some storms (Maruyama et al, 2004;Liu et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Ionospheric storm effects have been extensively studied on the basis of the observations of F 2 peak density ( N m F 2 ) and total electron content (TEC) [e.g., Prölss , ; Mendillo , ]. However, the topside ionospheric response to the storm is yet well explored, given that the topside ionospheric observations are relatively sparse [e.g., Lei et al ., , ; Gulyaeva and Stanislawska , , and references therein]. Although incoherent scatter radar (ISR) is a powerful tool for the direct measurement of ionosperic parameters from ionospheric E region to the topside ionosphere, the ISR sites and operational time are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Another method, which was used recently, is to combine ionospheric observations from ionosonde and ground‐based GPS receivers [e.g., Zhao et al ., ; Lei et al ., ]. The topside TEC above the F 2 peak height can be obtained from the difference between GPS TEC and bottomside electron content derived from ionosonde measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The nonlinear ionospheric and thermospheric responses depend on different geophysical factors. Although there are a number of publications on the subject (Cander, 2016;Klimenko et al, 2015;Lei et al, 2015;Blagoveshchensky et al, 2003;Szuszczewicz et al, 1998;Jin et al, 2008;Goncharenko et al, 2007), open questions still remain. These publications conclude that during a magnetic storm, at high latitudes the critical frequency of the ionopheric F2-layer is significantly decreased and there is additional sporadic ionization in the form of Es-layers.…”
mentioning
confidence: 97%